Implementasi Sekolah Lapang Iklim dan Dosis Pupuk Terhadap Karakter Kimia Tanah dan Hasil Jagung - Rifqi Ramadhani; Komariah Komariah; Sumani Sumani; Dwi Priyo Ariyanto (Agrosains : Jurnal Penelitian Agronomi, 2018)
Indonesian Agency for Meteorology Climatology and Geophysics Agency (BMKG) stated that the implementation of CFS program can increase the production significantly up to 30% (BMKG 2016). This research was conducted to know the influence of climate field school (CFS) and fertilizer dosage on soil chemical properties and corn yield. The study was conducted with a nested experimental design with two factors. Factor A has two levels: CFS Program (S1) and nonCFS (S2) and factor B was fertilizer dose. Factor B is nested on factor A as A (B). The fertilizer dose factor consists of 6 levels; T0 (without fertilizer); T1 (100% organic fertilizer); T2 (75% organic + 25% inorganic fertilizer); T3 (50% organic + 50% inorganic fertilizer), T4 (25% organic + 75% inorganic fertilizer), T5 (100% inorganic fertilizer). The results showed that CFS program increased available P, available K and soil pH, while fertilizer dose (50% organic fertilizer + 50% inorganic fertilizer) on CFS program yielded the highest soil organic matter (4.12%). CFS and fertilizer dose both did not affect the yield of maize significantly. However, the average yield of maize on CFS land is greater (6.50 tonha-1) compared to nonCFS (5.38 tonha-1). The treatment with 100% inorganic fertilizers) on CFS program gives highest yield (8.75 tonha-1).